(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
The Vine Mealybug Planococcus ficus (Signoret) (Hemiptera: Pseudococcidae ), is a serious pest of vineyards in the Mediterranean region, California and South Africa. In an attempt to develop a monitoring system for the mealybug, research teams in California and Israel have studied, independently, its pheromone system. The Californian team (Hinkens et al., 2001) identified (S)-lavandulyl senecioate (I) as the female sex pheromone of the mealybug. Lately, we identified (S)-lavandulyl isovalerate (Il) as an additional active component. The attraction of the vine mealybug males to both compounds was demonstrated by bioassays in petri dish arena and flight assays in the mealybug rearing room. Indoor, both compounds displayed a similar level of attractiveness to the massreared males. However, trials in a vineyard indicated that males were attracted only to compound I.